Solar-driven production of renewable chemicals via biomass hydrogenation with green methanol - Guangyu Chen; Cenfeng Fu; Wenhua Zhang; Wanbing Gong; Jun Ma; Xiaomin Ji; Lisheng Qian; Xuefei Feng; Chuansheng Hu; Ran Long; Yujie Xiong (Nature Communications)
Abstract Solar-driven, selective biomass hydrogenation is recognized as a promising route to renewable chemicals production, but remains challenging. Here, we report a TiO2 supported Cu single-atom catalyst with a four-coordinated Cu1−O4 structure, which can be universally applied for solar-driven production of various renewable chemicals from lignocellulosic biomass-derived platform molecules with good yields using green methanol as a hydrogen donor, to address this challenge. It is significant that the biomass upgrading driven by natural sunlight on a gram scale demonstrates the great practical potential. By combining in situ soft X-ray absorption spectroscopy with theoretical calculations, we successfully identify the dynamic evolution of Cu sites along with the biomass hydrogenation and methanol oxidation, where the tandem process is enabled by the photogenerated electrons and holes to complete a chemical cycle. The concept of solar-driven biomass hydrogenation proposed here provides an efficient and sustainable methodology for the sustainable production of renewable chemicals.